KOHESI GRAMATIKAL DAN LEKSIKAL PADA PIDATO MALALA YOUSAFZAI: â€œTHE PEN IS MIGHTIER THAN THE SWORDâ€ - AISYA, SITI (JURNAL ELEKTRONIK FAKULTAS SASTRA UNIVERSITAS SAM RATULANGI, 2018)
ABSTRACTÂ Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â  This researchentitled â€œGrammatical and Lexical Cohesion in Malala Yousafzaiâ€™s Speech: â€œThe Pen is Mightier than Swordâ€ is the requirement to accomplish the Bachelor Degree at Faculty of Humanities, Sam Ratulangi University. The objectives of this research are to identify, classify, and analyze descriptively the aspects of grammatical and lexical cohesion on the text of Malala Yousafzaiâ€™s speech. The theory used in this research is from Halliday and Hasan (1976). The theory focused on the aspects of grammatical and lexical cohesion.The grammatical cohesion consisted of reference(personal, demonstrative, interrogative pronoun), substitution, ellipsis, and conjunction.Â  The lexical cohesion consisted of reiteration (repetition, synonym, antonym, hyponym, meronymy) and collocation. The text of speech is taken from the internet at www.theirworld.org and other relevant source from internet as a source data.The result of this research shows that there are 102 pronouns which consist of 79 personal pronouns, 10 demonstrative pronouns, 13 interrogative pronouns, and there are 5 subtitusions, 83 conjuctions consist of 62 additive conjunctions, 5 adversative conjunctions, 8 causal conjunctions, 8 temporal conjunctions, and also in lexical cohesion there are 11 repetition, 16 synonym, 4 antonym, 1 hyponym, 3 meronymy, 5 collocation. There is no ellipsis found in the speech.-----------------------------------Keywords: Cohesion, Speech, Malala Yousafzai